In Memoriam, Solomon Marcus (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book commemorates Solomon Marcus’s fifth death anniversary with a selection of articles in mathematics, theoretical computer science, and physics written by authors who work in Marcus’s research fields, some of whom have been influenced by his results and/or have collaborated with him.